2008
DOI: 10.1021/es072017o
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Metallic Copper Nanoparticles at the Soil−Root Interface

Abstract: Copper is an essential element in the cellular electron-transport chain, but as a free ion it can catalyze production of damaging radicals. Thus, all life forms attempt to prevent copper toxicity. Plants diminish excess copper in two structural regions: rare hyperaccumulators bind cationic copper to organic ligands in subaerial tissues, whereas widespread metal-tolerant plants segregate copper dominantly in roots by mechanisms thought to be analogous. Here we show using synchrotron microanalyses that common we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(128 citation statements)
references
References 62 publications
4
123
1
Order By: Relevance
“…So far, the knowledge of the effect of nanoparticles on mycorrhizal fungi is very limited, only one study was carried out, where it was suggested that mycorrhizal fungi assisting plants can alleviate the toxicity of Cu by the formation of Cu nanoparticles and thus limiting its toxicity (Manceau et al, 2008). In the present paper nanoparticles were used according to manufacturer's instructions.…”
Section: S106mentioning
confidence: 99%
“…So far, the knowledge of the effect of nanoparticles on mycorrhizal fungi is very limited, only one study was carried out, where it was suggested that mycorrhizal fungi assisting plants can alleviate the toxicity of Cu by the formation of Cu nanoparticles and thus limiting its toxicity (Manceau et al, 2008). In the present paper nanoparticles were used according to manufacturer's instructions.…”
Section: S106mentioning
confidence: 99%
“…A whole host of nano-sensors are being developed that could revolutionize our understanding of our environment (e.g., Andreescu et al, 2009;Cho et al, 2008;Chopra et al, 2002;Consales et al, 2009;Granqvist et al, 2007;Huang and Chang, 2006;Liu and Lin, 2005;Nelli et al, 1996;Park et al, 2009;Toal et al, 2005), allowing us to detect environmental conditions, gas concentrations, and contaminant loads at a temporal and spatial resolution never before possible. As the tools for nanomaterial measurement and characterization are transferred into ecology, we are increasingly recognizing that many organisms produce nanoparticles, and that these natural nanoparticles may play important roles in biogeochemical cycling (e.g., Gorby et al, 2006;Manceau et al, 2008;Blango and Mulvey, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Bacterial reduction of uranyl, U 6+ (aq), to U(IV) oxide (uraninite) is an important bioremediation strategy (Bargar et al, 2008). Manceau et al (2008) found that wetland plants, or their symbionts, synthesize copper (Cu) nanoparticles in their rooting zone when grown in contaminated soils, thereby reducing Cu uptake. Dissimilatory metal-reducing bacteria even respire on iron oxide nanoparticles in anaerobic environments (Bose et al, 2009).…”
Section: Naturally Occurring Nanoparticles Are Ubiquitous In Naturementioning
confidence: 99%
“…Biomolecular responses to oxidative stress are therefore likely in yellow soil. Also present in bacterial surfaces, humic acid and natural organic matter, trace Cu(0) is expected to exist in the rhizosphere of E. splendens at the soil-root interface (Fulda et al, 2013;González et al, 2016;Manceau et al, 2008;Navarret et al, 2011). Cu(II) mainly complexes to carboxylic groups (Cu(II)-O/N), and adsorbed on root cell walls in E. splendens (Liu et al, 2014;Shi et al, 2004).…”
Section: Cu Isotopic Fractionation Between Neighboring Tissues In E mentioning
confidence: 99%